Predicting plant response to arbuscular mycorrhizas: The role of host functional traits. (April 2016) - Yang, Haishui; Xu, Jianglai; Guo, Yi; Koide, Roger T.; Dai, Yajun; Xu, Mingmin; Bian, Liping; Bian, Xinmin; Zhang, Qian
Abstract: The arbuscular mycorrhiza (AM) is among the most ubiquitous symbiosis in the world. A meta-analysis of 759 articles (1978–2012) was conducted to test whether ecologically important host plant traits (N-fixation and C-fixation pathway) affect the response of the plant to mycorrhizal colonization. We found that the effect of N-fixation on mycorrhizal growth response (MGR) depended on whether the plant was woody or a forb. N-fixing forbs had a higher MGR than non-N-fixing forbs, but the reverse was true for woody plants. Moreover, C4 -grasses had significantly higher MGR than C3 -grasses, but no significant difference was found between C3 and C4 forbs, or between C3 and C4 woody species. Overall, woody species had higher MGR than any other functional group. These results demonstrate that MGR does depend on host functional characteristics, but neither N-fixation capacity nor C-fixation pathway are apparently fundamental controllers of MGR. Instead, it would appear possible that these traits influence MGR only insofar as they influence more fundamental functions such as P demand and P supply.